Changes in lower uterine segment thickness during different gestational weeks in pregnant women qualified for trial of labor after cesarean section. Issue 3 (20th September 2021) - Rao, Jiaming; Fan, Dazhi; Chen, Ting; Lin, Dongxin; Ma, Huiting; Lu, Demei; Zeng, Meng; Liu, Yan; Guo, Xiaoling; Liu, Zhengping
Abstract: Objective: To investigate the correlation between lower uterine segment thickness (LUST) and gestational weeks (GW) in women who attempted trial of labor after cesarean section (TOLAC) and to estimate the reference ranges of LUST. Methods: A prospective cohort study was conducted between January 2019 and December 2020 at a tertiary‐care center in Foshan, China. A total of 2588 women who attempted TOLAC were included. LUST was measured in different trimesters using transabdominal ultrasound. Histograms were used to review the mean and standard deviations (SD) of LUST at different GW. Results: The mean LUST of the patients were 6.90 ± 2.86, 4.36 ± 1.87, 2.83 ± 0.65, and 2.57 ± 0.51 mm in the first (12.10 ± 1.28 weeks), second (21.79 ± 3.40 weeks), middle third (34.28 ± 2.64 weeks), and late third (38.20 ± 1.00 weeks) trimesters, respectively. An inverse correlation was noted between LUST and uterine rupture in women who underwent a planned ERCD ( P  < 0.001), but not in women who attempted TOLAC during the late third trimester ( P  = 0.629). Conclusion: LUST is inversely correlated with GW and decreases faster in the first and second trimesters than in the middle and late third trimesters. TOLAC should be approached with caution for pregnant women with a thin myometrium in late third trimester. Abstract : Lower uterine segement thickness measured by ultrasound is inversely correlated with gestation and decreases faster in the first two trimesters than in the third trimester.